2013
DOI: 10.1590/s2317-17822013000400004
|View full text |Cite
|
Sign up to set email alerts
|

Comunicação em adultos surdocegos com síndrome de Usher: estudo observacional retrospectivo

Abstract: OBJETIVO: Conhecer as características e desafios enfrentados por surdocegos para comunicar-se e locomover-se; avaliar as repercussões da surdocegueira na vida dos sujeitos, especialmente em relação à comunicação e locomoção. MÉTODOS: Relato de série de casos realizado a partir de entrevistas semiestruturadas com questões relativas à funcionalidade da comunicação, com indivíduos com diagnóstico clínico de síndrome de Usher que frequentaram um ambulatório especializado em um serviço universitário, durante o ano … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
(23 reference statements)
1
5
0
1
Order By: Relevance
“…Authors also reported that alternative means of communication such as signing, braille, print on palm, Tadoma (method of communication that involves individual with deafblindness placing their thumb on a speaker’s person's lips and their fingers along the jawline to feel their movements as they speak [ 6 ], and assistive technology such as computer/interpreter-facilitated communication means, videophone technology, and cochlear implants facilitated communication and social interactions of persons with deafblindness [ 32 , 41 , 43 – 45 ]. Additionally, strategies such as prior rehearsal of situations, use of communication repair strategies (for example asking for repetition or further clarifications from the conversational partner) and recreational activities could also be helpful in enabling successful communication [ 34 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Authors also reported that alternative means of communication such as signing, braille, print on palm, Tadoma (method of communication that involves individual with deafblindness placing their thumb on a speaker’s person's lips and their fingers along the jawline to feel their movements as they speak [ 6 ], and assistive technology such as computer/interpreter-facilitated communication means, videophone technology, and cochlear implants facilitated communication and social interactions of persons with deafblindness [ 32 , 41 , 43 – 45 ]. Additionally, strategies such as prior rehearsal of situations, use of communication repair strategies (for example asking for repetition or further clarifications from the conversational partner) and recreational activities could also be helpful in enabling successful communication [ 34 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Those with acquired condition (Group 2) often experienced embarrassment due to frequent bumping into objects/people, and rejected use of assistive devices such as canes and hearing aids in public due to perceptions of stigma [ 6 , 32 , 33 , 41 , 49 ]. With reference to older adults (Group 3), lack of independence in indoor-outdoor mobility was found to exacerbate feelings of social isolation, caused by communication challenges [ 37 , 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations